Development and Initial Validation of the Impression Motivation in Sport Questionnaire–Team - Payne, S.; Hudson, J.; Akehurst, S.; Ntoumanis, Nikos (Human Kinetics, 2013)
Impression motivation is an important individual difference variable that has been under-researched in sport psychology, partly due to having no appropriate measure. This study was conducted to design a measure of impression motivation in team-sport athletes. Construct validity checks decreased the initial pool of items, factor analysis (n = 310) revealed the structure of the newly developed scale, and exploratory structural equation modeling procedures (n = 406) resulted in a modified scale that retained theoretical integrity and psychometric parsimony. This process produced a 15-item, 4-factor model; the Impression Motivation in Sport Questionnaire-Team (IMSQ-T) is forwarded as a valid measure of the respondent's dispositional strength of motivation to use self-presentation in striving for four distinct interpersonal objectives: self-development, social identity development, avoidance of negative outcomes, and avoidance of damaging impressions. The availability of this measure has contributed to theoretical development, will facilitate research, and offers a tool for use in applied settings.